2016
DOI: 10.18296/cm.0016
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing parental involvement in student learning

Abstract: There is much international evidence that parental involvement in children's learning can positively influence achievement. New Zealand policy expects schools to nurture such involvement, particularly in relation to Máori and Pasifika learners. Despite policy imperatives and valuable professional development projects, such involvement has proved challenging to embed within many English-medium school settings. We examined policy, theoretical, and research literature to identify key supports and barriers to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Reviews of these programmes found that despite thorough planning, parents indicated they needed more time and explicit explanations to fully understand assessment, curriculum levels, and teaching aims (Fisher and Neill 2006;Trinick 2015). These findings demonstrate that communicating information about mathematics learning is likely to be much more complex than many teachers and schools realize, especially in the context of reform in mathematics (Averill et al 2016;Remillard and Jackson 2006).…”
Section: Conceptual Framework and Literature Backgroundmentioning
confidence: 92%
See 4 more Smart Citations
“…Reviews of these programmes found that despite thorough planning, parents indicated they needed more time and explicit explanations to fully understand assessment, curriculum levels, and teaching aims (Fisher and Neill 2006;Trinick 2015). These findings demonstrate that communicating information about mathematics learning is likely to be much more complex than many teachers and schools realize, especially in the context of reform in mathematics (Averill et al 2016;Remillard and Jackson 2006).…”
Section: Conceptual Framework and Literature Backgroundmentioning
confidence: 92%
“…As the key stakeholder in these events, arguably parents should lead such decisions. Averill et al (2016) discuss the inconsistencies and lack of direction in policies that expect the involvement of families; here, we see this played out in the challenge to manage the concurrent Ministry directives of involving students in the reporting process (e.g., MOE 2007MOE , 2018c and being responsive to the needs and desires of families (e.g., MOE 2019).…”
Section: Areas Of Tensionmentioning
confidence: 95%
See 3 more Smart Citations